(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article reveals the essence of the competitiveness of future specialists in the management foreign economic activity of the aviation industry as an object of pedagogical research. The relevance of the chosen perspective is due to the high level of dependence of the results of activities of both higher educational institutions and their graduates on the level of competitiveness of specialists in the labor market. Therefore, the most important condition for the development and effectiveness of the object and subject of educational activity is the determination of the composition of this indicator for future professionals as an indicator of the quality of educational services and the basis for ensuring the organizational and pedagogical conditions of the educational process. The main part of the article is based on the findings of researchers and scientific and practical publications on competencies and professional competence, as the basis for the formation of competitiveness. In addition, scientists’ approaches to the selection of components, their justification and grouping were analyzed. The basis for identifying the components of competitiveness of future specialists is, first of all, the functional purpose, the source of origin, the nature of origin and the subject of future activities, the successful implementation of which requires certain abilities, character traits, moral attitudes, skills or theoretical knowledge. The important conclusions of the article were the selection of the component of competitiveness of the manager of foreign economic activity of an enterprise in the aviation industry on the basis of achieving training and development goals in 4 main areas: personal self-determination, future professional activity, social role, readiness to work in a competitive environment. Thus, the main components of the conceptual model of competitiveness of the manager of foreign economic activity in the aviation industry can be called: cognitive-activity, as the combination of basic knowledge for the formation of skills and abilities of the future professional activity; praxeological-reflexive, implying the formation of a personality system of values ​​and personal orientations; social communicative is the ability to social relations and interpersonal interaction; acmeological, which is based on the development of the personality at the stage of becoming of maturity, the desire for professional self-realization and personal achievements. Structural component system, the composition and relations in which reflect the characteristics and specifics of the activities of the aviation specialist in foreign economic activity can be used to develop a model for preparing students in an educational institution.